Altrenogest and fat for summer breeding of first-litter sows - Stevenson, Jeffrey S.; Davis, Duane L.; Pollmann, D.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred first-Iitter sows in a commercial swine unit were assigned to serve as controls after summer weanings or were fed altrenogest for 7 days or altrenogest for 7 days plus supplemental fat for 14 days after weaning. While similar proportions of sows came into heat after weaning, sows fed altrenogest returned to estrus about 9 days later than control sows. Incidence of anestrus was similar across sow groups (31%), while most of the sows not detected in heat could be classified by cause after examining serum progesterone concentrations at 3 wk after weaning. Nearly 69 % of the sows not detected in heat had luteal function, indicating a failure to detect sows when in true estrus or failure of sows to show behavioral estrus. Farrowing traits were similar among treatments, however, there was a tendency for sows fed altrenogest to have higher farrowing rates.
Keywords: Swine; Altrenogest; Fat; First-litter sows